AL-TA’AMUL MA’A AL-ĀKHAR FĪ ḌAW’ DIRĀSĀT ‘ULAMĀ’ AL-MUSLIMĪN LI AL-ADYĀN - Nur Baety Sofyan (Universitas Islam Negeri Ar-Raniry, 2016)
This research aims to publicize how to deal with the other religions in the light of muslim scholars studies. The Researcher followed the inductive approach in the presentation of information concerning the definition of manhaj idiomatically and opinions of scientists to interpret the verses of the Koran and also the analytical approach was employed to study the manhaj used by scientists in dealing with other religions. The researcher came first pages in the definition of the manhaj idiomatically from within the books of various religions and the statement of the scientists in the interpretation of Quranic verses about dealing with the other non-Muslims. Besides, the researcher also mentioned and elaborated more about the most important methods used by scientists in dealing with other religions. The researcher ends the study with conclusions that can be summarized in two main points: first: the manhaj is organized plan for several intellectual or sensory processes in order to uncover the truth or proof of it, and is also the pillars of the task and the foundations on which describes the behavior of an individual, community or nation to achieve effects that aspire to each group; Second, Muslim scholars were applied numerous methods or manhaj in their study of religions, including historical descriptive approach and the methodology of analysis and comparison, the methodology of description and statement, case analytical approach, and the approach of arguing and debating.